RISALAH TEORI-TEORI KOMUNIKASI MASSA - Puji Laksono (Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
Mass communication is the communication from a person or group of people through a sender (media) to audiences or markets. Mass communication in practice is the dissemination of information through mass media, such as television, radio, newspapers, internet social media which are able to disseminate information widely to the public. Information in the process of mass communication is spread simultaneously throughout the radius of the coverage of the mass media used. The completeness of technical equipment determines the dissemination of information. Denis McQuail suggests that everyone practices or participates in the process of mass communication. Not everyone is connected to the mass media. So the higher up the fewer people who participate in the process of mass communication. In the process of mass communication, the theorizing process in particular has been put forward by many scientists through the research process. The theory is understood as a series of related statements designed to explain a particular phenomenon or a category of related symptoms. With a theory, a phenomenon can be explained scientifically. The theories of mass communication are agenda-setting theory, cultivation theory, spiral of silence theory, use, and satisfaction theory, technological determinism, bullet theory, innovation diffusion theory, critical media theory, cultural imperialism theory, and media equality theory. With a theory, a phenomenon can be explained scientifically.